Advances in PET imaging of ischemic stroke - Orhii, Paulette D.; Haque, Muhammad E.; Fujita, Masahiro; Selvaraj, Sudhakar (Frontiers in Stroke, 2023)
Ischemic strokes make up 87% of all cerebrovascular events. Intravenous trans-plasminogen (tPA), a thrombolytic agent, has been recognized as the only viable option for patients with ischemic stroke if administered within 3.5 hours of onset and increases the risk of hemorrhagic transformation if administered beyond the treatment window. Acute treatment strategies are centered around rescuing salvageable penumbra. Molecular imaging using positron emission tomography (PET) has shown higher sensitivity and specificity than CT and MRI in delineating penumbral tissues. In addition, PET imaging has identified the role of key inflammatory mediators in atherosclerosis, cellular damage, and recovery. Recently, a novel PET imaging study has shown an investigating synaptic density in subacute stroke. Lastly, novel PET radiotracers have been developed to further explore biochemical mechanisms implicated in stroke pathophysiology. Further investigation with PET is needed to understand stroke mechanisms and advance pharmacologic treatment.